2003
DOI: 10.1139/x03-154
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon effects on litterfall in a subtropical forest

Abstract: The litterfall in a subtropical broadleaf forest within the Fushan Experimental Forest in northeastern Taiwan was monitored for 9 years. Mean annual litterfall was very sensitive to typhoon frequency and intensity, ranging from 3 to 11 Mg·ha -1 ·year -1 . Litterfall was significantly higher in years with strong typhoons than in years without typhoons, and the number of strong typhoons explained 82% of interannual variation in litterfall. Nutrient-use efficiency (dry mass/nutrients in litterfall) was high for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 32 publications
4
63
0
1
Order By: Relevance
“…2) in agreement with other studies (Xu et al, 2000;Lin et al, 2003;Saarsalmi et al, 2007;Li et al, 2010). The annual litterfall rate among the mixed forests ranged from 76 to 335 g DW m -2 year -1 , implying that variation in the litterfall rate exists even in forests of the same dominant species (Gairola et al, 2009 partly induced by human errors.…”
Section: Interannual Variation Of Annual Litterfall Ratesupporting
confidence: 90%
See 2 more Smart Citations
“…2) in agreement with other studies (Xu et al, 2000;Lin et al, 2003;Saarsalmi et al, 2007;Li et al, 2010). The annual litterfall rate among the mixed forests ranged from 76 to 335 g DW m -2 year -1 , implying that variation in the litterfall rate exists even in forests of the same dominant species (Gairola et al, 2009 partly induced by human errors.…”
Section: Interannual Variation Of Annual Litterfall Ratesupporting
confidence: 90%
“…In addition, there was a significant positive correlation at the Dc site between the annual litterfall rate and the number of windy days during the growing season or autumn in the current year. These phenomena are easily understandable compared with the relationship between spring solar radiation and the annual litterfall rate, because several researches already reported that strong wind (Christensen, 1975;Lin et al, 2003) or low air temperature (Battaglia et al, 1998) enhances the litterfall rate.…”
Section: Interannual Variation Of Annual Litterfall Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Mean soil MBC in the CTDD plots was significantly higher than in the control plots in every sampling week, except for the three weeks before the treatment and the 96th week after the treatment. A sudden deposition of massive hurricane-induced litterfall in various forests was shown to increase soil carbon input and the heterogeneity of the microenvironment for soil microbes [5], change soil C/N ratios [3,8], increase and then decrease competition for soil nutrients between soil microorganisms and plant species [23,57], and alter the biomass and biodiversity of litter invertebrates [14], all of which could be potential factors that might have jointly elevated soil MBC. These potential factors in the CTDD plots may lead to a persistent higher soil MBC in the CTDD plots.…”
Section: Discussionmentioning
confidence: 99%
“…Natural disturbances often deposit massive amounts of litterfall in forests, such as in the case of drought [1], wind [2], rainstorms [3], and ice storms [4]. Severe hurricane-force winds instantaneously…”
Section: Introductionmentioning
confidence: 99%